The hopes and fears of attendance work and problematic school absenteeism: notes on the politics of expertification - Martin Harling; Ola Strandler (Education Inquiry)
This study explores problematic school absenteeism (PSA) in Swedish education, focusing on how schools conceptualise and address this complex issue. Drawing on a case study of one secondary school using discursive institutionalism (DI), it examines how ill-defined problems like PSA are framed, analysing how cognitive and normative ideas shape institutional responses. PSA is addressed at the school through three “hopes”: pedagogical, social, and psychological. The subject didactic collegium model (SDC), originally a pedagogical model for improving teaching, has become a “pedagogical hope”, aimed at re-engaging absent students by enhancing motivation and addressing academic challenges. Simultaneously, non-teaching responsibilities are delegated to paraprofessionals, creating a “social hope” that enables teachers to focus on core teaching tasks. Lastly, specialised teaching groups, or “smaller contexts”, represent a “psychological hope”, offering segregated support for students with severe absenteeism or neuropsychiatric diagnoses. While these approaches provide structure, the study highlights risks of expertification, where fragmented professional domains hinder collaboration and fail to address the multifaceted causes of PSA. The findings argue for more holistic and relational strategies that consider the full complexity of students’ needs. This research contributes to discussions on school absenteeism and broader debates on professional expertise and governance in education.